The Production of Ligninolytic Enzymes by Marine-Derived Basidiomycetes and Their Biotechnological Potential in the Biodegradation of Recalcitrant Pollutants and the Treatment of Textile Effluents - Bonugli-Santos, Rafaella C.; Durrant, Lucia Regina; Sette, Lara Duraes [UNESP] (Springer, 2012)
Filamentous fungi derived from marine environments are well known as a potential genetic resource for various biotechnological applications. Although terrestrial fungi have been reported to be highly efficient in the remediation of xenobiotic pollutants, fungi isolated from the marine environment may possess biological advantages over terrestrial fungi because of their adaptations to high salinity and pH extremes. The present study describes the production of ligninolytic enzymes under saline and non-saline conditions and the decolorization of Remazol Brilliant Blue R (RBBR) dye by three basidiomycetes recovered from marine sponges (Tinctoporellus sp. CBMAI 1061, Marasmiellus sp. CBMAI 1062, and Peniophora sp. CBMAI 1063). Ligninolytic enzymes were primarily produced by these fungi in a salt-free malt extract and malt extract formulated with artificial seawater (saline condition). CuSO4 and wheat bran were the best inducers of lignin peroxidase and manganese peroxidase activity. RBBR was decolorized up to 100% by the three fungi, and Tinctoporellus sp. CBMAI 1061 was the most efficient. Our results revealed the biotechnological potential of marine-derived basidiomycetes for dye decolorization and the treatment of colored effluent as well as for the degradation of other organopollutants by ligninolytic enzymes in non-saline and saline conditions that resemble the marine environment.
Keywords: Marine-derived fungi; Basidiomycetes; Dye decolorization; Ligninolytic enzymes; Biotechnological applications